The Relationship Between Optimism and Educational Support With Subjective Well-Being Psychological Training in Paskhas Air Force Adisucipto Yogyakarta - Derita Perhatian (STMIK Indonesia Banda Aceh, 2025)
In carrying out their duties with full professionalism to protect the Republic of Indonesia for the integrity of the Indonesian State, TNI members certainly also want education in Subjective Well-Being (SWB) training. This study aims to determine (1) the relationship between optimism and SWB, (2) the relationship between educational support and SWB training, (3) the relationship between optimism and educational support with SWB training. The research data collection method uses a scale consisting of the SWB scale, optimism scale, and educational support scale with exercise Alpha reliability of 0.946, 0.915 and 0.929. The sample in this study were 100 members of the Adisucipto Paskhas TNI who were taken with simple random sampling technique. Data analysis techniques in this study using product moment correlation techniques and regression analysis. The results of the analysis show that there is a relationship between (1) optimism with SWB with a coefficient value of 0.669 (p <0.05), (2) educational support with SWB, with a correlation value of 0.778 (p <0.05) and (3) optimism and educational support with SWB training, R value of 0.814 (p <0.05) which means that the two predictor variables can contribute in predicting SWB by 66.3%% while the remaining 33.7% is influenced by other factors not examined in this study.